2011
DOI: 10.1159/000324106
|View full text |Cite
|
Sign up to set email alerts
|

Role of Preoperative and Intraoperative Factors in Mediating Infection Complication following Percutaneous Nephrolithotomy

Abstract: Objective: To identify the pre- and intraoperative factors that affect the development of postoperative systemic inflammatory response syndrome (SIRS) following percutaneous nephrolithotomy (PCNL). Patients and Methods: A total of 200 patients were treated with PCNL, 56 of which developed postoperative SIRS (group I) and 144 did not (group II). For these 2 groups, the patient factor, operative factor, preoperative urine culture, pelvic urine culture, and stone culture were compared. Results: Average age, stone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
32
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 31 publications
(31 reference statements)
5
32
2
Order By: Relevance
“…The higher incidence of sepsis following PCnL in elderly may be explained by the higher positive preoperative urine culture compared with those in younger patients even though it is not significantly different. The criteria of the postoperative sepsis is defined as systemic inflammatory response syndrome (SIRS) which presents more than one of the following clinical findings: body temperature > 38 °C or < 36 °C, heart rate > 90 beats per minute, respiratory rate > 20 breaths per minute or PaCO 2 < 32 mmHg, and white blood cell count > 12,000/cu mm, < 4000/cu mm (16). Three of 4 elderly patients with postoperative sepsis had E-coli (ESBL) positive in the preoperative urine culture, and one patient had changed to new antibiotic based on evidence from intraoperative stone culture.…”
Section: Discussionmentioning
confidence: 99%
“…The higher incidence of sepsis following PCnL in elderly may be explained by the higher positive preoperative urine culture compared with those in younger patients even though it is not significantly different. The criteria of the postoperative sepsis is defined as systemic inflammatory response syndrome (SIRS) which presents more than one of the following clinical findings: body temperature > 38 °C or < 36 °C, heart rate > 90 beats per minute, respiratory rate > 20 breaths per minute or PaCO 2 < 32 mmHg, and white blood cell count > 12,000/cu mm, < 4000/cu mm (16). Three of 4 elderly patients with postoperative sepsis had E-coli (ESBL) positive in the preoperative urine culture, and one patient had changed to new antibiotic based on evidence from intraoperative stone culture.…”
Section: Discussionmentioning
confidence: 99%
“…Appropriate therapy was a continuum of management of infection ranging from drainage (opening the nephrostomy tube) and broad-spectrum antibiotics to aggressive fluid resuscitation and invasive monitoring with medical management in the intensive care setting until the causative agent was found and eradicated [5,6] . Vital signs, pulse oximetry, urine output, and initial laboratory testing were continuously monitored to assess the severity of global tissue hypoxia and organ dysfunction [7,8] .…”
Section: Risk Factors For Septic Shockmentioning
confidence: 99%
“…They noted no colonic injury in their study. Lojanapiwat and Kitirattrakarn [11] assessed the pre- and intraoperative factors influencing the occurrence of postoperative systemic inflammatory response syndrome (SIRS) after PCNL. They demonstrated that positive preoperative urine culture, pelvic urine culture and stone culture were significantly more prevalent in patients with a development of SIRS after PCNL than in patients without this complication; they concluded that these positive cultures are important factors that can predict the postoperative SIRS.…”
Section: Discussionmentioning
confidence: 99%